Improving English writing skills using social support slogans - Gutirrez Huancayo, Vladimir Romn (Studies in English Language and Education, 2025)
This research aims to study English writing competencies in 88 students enrolled in three professional programs production mechanics, automotive mechanics, and electrical engineering from a public technological institute in Peru, after implementing a program of social support slogans. This research adopted a mixed-method design with the quantitative stage divided into three parts. The first stage determined the differences in English writing competences between the three student groups assigned based on their professional programs, and the second stage was to understand how these study groups differ according to their elements of divergent thinking. Finally, the last quantitative stage validated a model considering two constructs: program benefits (PB) and type of posters (KP). Meanwhile, the qualitative data was obtained using an open-ended survey distributed to these students. The results show that the medians are not statistically significant for writing competencies, based on the Kruskal-Wallis test (sig. 0.200). Second, the clustering results highlighted the originality, although three different conglomerates were formed. Third, an acceptable factorial structure was achieved for the proposed fit model (RMSEA 0.045; CFI 0.968; and TLI 0.957). Likewise, the data from the open-ended questionnaire was coded into writing improvement, social dimension and innovative activity. They valued the poster project for improving English writing while applying knowledge to issues such as workplace safety and energy saving. They also emphasized its innovative and creative nature. Poster design encouraged greater reading and analysis of English texts, supporting better writing, with outcomes linked to poster types: emotional, informational, companionship, or tangible.